2019
DOI: 10.1371/journal.pone.0215843
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional GPU-accelerated active contours for automated localization of cells in large images

Abstract: Cell segmentation in microscopy is a challenging problem, since cells are often asymmetric and densely packed. Successful cell segmentation algorithms rely identifying seed points, and are highly sensitive to variablility in cell size. In this paper, we present an efficient and highly parallel formulation for symmetric three-dimensional contour evolution that extends previous work on fast two-dimensional snakes. We provide a formulation for optimization on 3D images, as well as a strategy for accelerating comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For practicality and efficiency, we focused on thin (10 μm) slices that are imaged two-dimensionally to avoid antibody/dye penetration limitations and complexities associated with 3D imaging and automated image analysis 24 . The proposed computational pipeline is specifically designed to generate 2D immunohistology results from individual whole-brain slices which is expandable for 3D segmentation 25 and reconstruction 26 to better understand the connectome of brain cytoarchitecture at cellular, niche, and organ levels 27 . Cellular measurements are exported to flow cytometry standard (FCS) and Image Cytometry Experiment (ICE) file formats for visualization and statistical profiling using common commercially available software tools (e.g., FCS Express, De Novo Software; FlowJo, BD Biosciences, Kaluza, Beckman Coulter, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…For practicality and efficiency, we focused on thin (10 μm) slices that are imaged two-dimensionally to avoid antibody/dye penetration limitations and complexities associated with 3D imaging and automated image analysis 24 . The proposed computational pipeline is specifically designed to generate 2D immunohistology results from individual whole-brain slices which is expandable for 3D segmentation 25 and reconstruction 26 to better understand the connectome of brain cytoarchitecture at cellular, niche, and organ levels 27 . Cellular measurements are exported to flow cytometry standard (FCS) and Image Cytometry Experiment (ICE) file formats for visualization and statistical profiling using common commercially available software tools (e.g., FCS Express, De Novo Software; FlowJo, BD Biosciences, Kaluza, Beckman Coulter, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of DL models is that they can handle large high-dimensional data such as hyperspectral images. Several studies have reported that the use of DL in HSI improved the classification accuracy, computational efficiency, and robustness to noise and solved other challenges [ 13 , 19 , 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of DL models is that they can handle large high-dimensional data such as hyperspectral images. Several studies have reported that the use of DL in HSI improved the classification accuracy, computational efficiency, and robustness to noise and solved other challenges [13,19,20] Recently, a generative adversarial network (GAN) was used for anomaly detection [21,22] in an unsupervised way. Jiang et al [21] proposed a GAN-based anomaly detection model for hyperspectral images in remote sensing, where anomaly suppressed hyperspectral images were reconstructed and a detection map was predicted by using differences between the original and reconstructed images.…”
Section: Introductionmentioning
confidence: 99%